Learning-based vertebra localization and labeling in 3D CT data of possibly incomplete and pathological spines - Jakubicek, Roman; Chmelik, Jiri; Jan, Jiri; Ourednicek, Petr; Lambert, Lukas; Gavelli, Giampaolo (Computer methods and programs in biomedicine, 2020)
BACKGROUND AND OBJECTIVE: We present a fully automatic system based on learning approaches, which aims to localization and identification (labeling) of vertebrae in 3D computed tomography (CT) scans of possibly incomplete spines in patients with bone metastases and vertebral compressions. METHODS: The framework combines a set of 3D algorithms for i) spine detection using a convolution neural network (CNN) ii) spinal cord tracking based on combination of a CNN and a novel growing sphere method with a population optimization, iii) intervertebral discs localization using a novel approach of spatially variant filtering of intensity profiles and iv) vertebra labeling using a CNN-based classification combined with global dynamic optimization. RESULTS: The proposed algorithm has been validated in testing databases, including also a publicly available dataset. The mean error of intervertebral discs localization is 4.4 mm, and for vertebra labeling, the average rate of correctly identified vertebrae is 87.1%, which can be considered a good result with respect to the large share of highly distorted spines and incomplete spine scans. CONCLUSIONS: The proposed framework, which combines several advanced methods including also three CNNs, works fully automatically even with incomplete spine scans and with distorted pathological cases. The achieved results allow including the presented algorithms as the first phase to the fully automated computer-aided diagnosis (CAD) system for automatic spine-bone lesion analysis in oncological patients.
Keywords: Imaging, Three-Dimensional; Software; počítačová rentgenová tomografie; software; Diagnosis, Computer-Assisted; Convolution neural network; Humans; nádory kostí; Algorithms; diagnóza počítačová; Vertebra detection; rozpoznávání automatizované; neuronové sítě; nemoci páteře; Bone Neoplasms; databáze faktografické; Neural Networks, Computer; lidé; počítačové zpracování obrazu; Image Processing, Computer-Assisted; reprodukovatelnost výsledků; Learning-based approach; Databases, Factual; Neoplasm Metastasis; Intervertebral Disc; metastázy nádorů; Spinal Diseases; Spine; Pathological vertebrae; Reproducibility of Results; Tomography, X-Ray Computed; Pattern Recognition, Automated; algoritmy; zobrazování trojrozměrné; páteř; meziobratlová ploténka